Estimation of the time since death in decomposed bodies found in Australian conditions. Issue 1 (2nd January 2017) - Hayman, Jarvis; Oxenham, Marc
Abstract : This paper proposes a new method for estimating time since death (TSD) in individuals found between 0 and 14 days subsequent to death indoors. The method is retrospective and involved (1) access to autopsy (and other) reports held by Australia's National Coronial Information System (NCIS); (2) selection of cases in the NCIS that included detailed descriptions of the degree of decomposition of various body organs as well as reliable information on TSD; (3) development of a systematic and quantitative way of scoring the degree of decomposition in body organs (the total body decomposition score, or TBS); (4) development of models to accurately estimate TSD from determinations of TBS; and (5) testing of these models. A series of Australian State and Territory as well as winter and summer season specific models for estimating TSD were generated. These models, particularly those based on TBS, are accurate to within several hours to half a day of death in most instances. While these models are regionally specific, the methodology can be used on any appropriate data set to generate TSD estimation equations.